2022
DOI: 10.3389/fonc.2022.918331
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Therapeutic Vaccines for Precancerous Cervical Lesions: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThis study systematically evaluated the effectiveness and safety of therapeutic vaccines for precancerous cervical lesions, providing evidence for future research.MethodsWe systematically searched the literature in 10 databases from inception to February 18, 2021. Studies on the effectiveness and safety of therapeutic vaccines for precancerous cervical lesions were included. Then, we calculated the overall incidence rates of four outcomes, for which we used the risk ratio (RR) and 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…This permitted us to provide a robust estimate of the efficacy of therapeutic vaccines against the most important endpoint of regression of high-grade lesions. A recently published systematic review of therapeutic vaccines showed that the overall incidence rate of CIN 2/3 regression induced by the vaccines (52.08%; 95% CI 42.08% to 62.01%) was comparable to our study 43…”
Section: Discussionsupporting
confidence: 89%
“…This permitted us to provide a robust estimate of the efficacy of therapeutic vaccines against the most important endpoint of regression of high-grade lesions. A recently published systematic review of therapeutic vaccines showed that the overall incidence rate of CIN 2/3 regression induced by the vaccines (52.08%; 95% CI 42.08% to 62.01%) was comparable to our study 43…”
Section: Discussionsupporting
confidence: 89%
“…This result is consistent with previous findings of similar meta-analyses conducted in 2020–2022 and involving 9–11 studies with pooled VE outcomes ranging between 46 and 65% regardless of timing of vaccination. 11 12 24–26 It is likely that the nine additional studies in our PAVIVE Study did not affect the overall result showing robustness and benefit of HPV vaccination against CIN2+ recurrence irrespective of the HPV genotype. Moreover, another two meta-analyses evaluating recurrence rates for only vaccine genotypes of HPV16 and 18, confirmed a 63–73% reduction in CIN2+ recurrence rates.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, we followed up on the recently published metaanalyses and reviews in an attempt to establish, specifically, an association (if any) between timing of vaccination and surgical excision with regard to the outcome. [11][12][13][14]…”
Section: Systematic Reviewmentioning
confidence: 99%
“…However, this estimate may be overestimated by including in their analysis both prophylactic and therapeutic vaccines, as the two vaccines have entirely different modes of action. 39 To conclude, the modest efficacy of the therapeutic vaccines in the treatment of high-grade cervical cancer precursors may not justify replacing the highly effective ablative or excisional treatment with these new interventions. The existing vaccines may be made more effective through innovative approaches for treatment such as use of peptide-based vaccines to boost the effect of virus-based vaccines to overcome the anti-vector immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, this estimate may be overestimated by including in their analysis both prophylactic and therapeutic vaccines, as the two vaccines have entirely different modes of action. 39…”
Section: Discussionmentioning
confidence: 99%